FAKTOR-FAKTOR YANG DAPAT MEMENGARUHI PRAKTIK MANAJEMEN LABA PADA PERUSAHAAN NON-KEUANGAN - Yosua Tiara Wiharja; Indra Arifin Djashan (E-Jurnal Akuntansi TSM, 2022)
The purpose of this research is to obtain empirical evidence about the impact of independent commissioners, audit committee, size audit, expert audit, activities audit, audit committee meetings, and female directors on earning management. The populations on this research are non-financial companies listed in Indonesia Stock Exchange from 2018 to 2020. This research used multiple regression method to analyze data and by purposive sampling method for sampling technique. The result of the sampling there are 101 non-financial companies that are qualified to be taken as research sample. This research finds that independent commissioners, audit committee, size audit, expert audit, activities audit, audit committee meetings, and female directors have no effect on earnings management